Modified acrylate polymer as well as preparation method and application thereof

By introducing modified acrylate polymers into the lithium-ion battery separator materials, the high temperature and mechanical strength of the material are improved by using aromatic groups and polar groups, and the electrolyte wetting properties are optimized through side chains, the shortcomings of existing separator materials in temperature resistance and electrolyte wetting properties are solved, and higher battery safety and energy density are achieved.

CN119613592AActive Publication Date: 2025-03-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510146889.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-03-14
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

The existing lithium-ion battery separator materials have shortcomings in temperature resistance and electrolyte infiltration performance, and it is difficult to take into account high temperature stability and good electrolyte liquid absorption and liquid retention performance.

Method used

A modified acrylate polymer is developed with a structure that increases the glass transition temperature and mechanical strength by introducing aromatic and polar groups and optimizes the electrolyte wetting through side chain substituents.

Benefits of technology

The excellent high temperature resistance and good electrolyte infiltration performance of modified acrylate polymer in lithium-ion battery separator coating are achieved, and the safety and energy density of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613592A_ABST
    Figure CN119613592A_ABST
Patent Text Reader

Abstract

The invention discloses a modified acrylate polymer as well as a preparation method and application thereof, and belongs to the technical field of lithium ion battery materials. The modified acrylate polymer provided by the invention is simple in preparation method, easy to synthesize, high in reaction product yield, low in preparation cost and excellent in environmental protection performance, a lithium ion battery diaphragm coating prepared from the modified acrylate polymer provided by the invention has good electrolyte infiltration performance, the internal resistance of a battery can be reduced, and the service life of the battery is prolonged. The rate capability and the discharge capacity of the battery are improved; meanwhile, the high-temperature-resistant performance is good, and the safety and the reliability of the battery in a high-temperature environment or when the battery is overheated can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and more specifically, to a modified acrylate polymer and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are important green energy batteries. Due to their light weight, large specific capacity and safety, they have been widely used in mobile power supplies, laptops, mobile phones, electric vehicles and other fields. Lithium-ion batteries are generally composed of packaging materials, positive electrodes, negative electrodes, diaphragms and electrolytes. Among them, the diaphragm is an important material for isolating the positive and negative electrodes in the battery core. During the use of the battery, lithium ions can freely pass through the diaphragm to realize the charging and discharging of the battery. The quality of the diaphragm is directly related to the service life and safety performance of the battery.

[0003] The diaphragm materials used in commercial lithium-ion batteries are often based on polyethylene and polypropylene. Such materials have the disadvantage of poor temperature resistance, and as non-polar materials, their electrolyte absorption and retention properties are poor. Therefore, it is common to coat aramid, PVDF-HFP, inorganic coating materials and other materials on the diaphragm base film to improve the thermal stability of the diaphragm, liquid absorption and retention, and electrode adhesion, thereby improving battery safety, energy density, rate discharge, cycle life, etc. However, among the above coating materials, aramid special coating materials have the best high temperature resistance, but the cost is very expensive; PVDF-HFP has good electrolyte wettability and high temperature resistance, but due to environmental protection reasons, its raw materials are strictly controlled and the price is also expensive; inorganic coating materials such as Al 2 O 3 It has cost advantages, but there are problems such as powder easy to fall off, pore clogging and high density resulting in low battery energy density.

[0004] Existing polyacrylate materials, such as polymethyl methacrylate (PMMA), are low-priced and have good electrolyte wettability, but they are not resistant to high temperatures (PMMA's maximum continuous use temperature varies between 65°C and 95°C depending on working conditions, and its heat deformation temperature is about 96°C), making them unsuitable for direct use as battery separator coating materials.

[0005] Therefore, there is an urgent need to develop diaphragm coating materials that have both electrolyte wetting properties and high temperature resistance. Summary of the invention

[0006] The purpose of the present invention is to overcome the above-mentioned defects of the prior art and provide a modified acrylate polymer and a preparation method and application thereof. The modified acrylate polymer of the present invention has both excellent high temperature resistance and good electrolyte wetting performance, and can be used as a lithium ion battery separator coating material.

[0007] To achieve the above object, the technical solution of the present invention is as follows: A modified acrylic ester polymer, the structure of the polymer is shown in formula (1):

[0008] Wherein, the main chain substituent R of the polymer 1 Selected from C 1 -C 10 One of an alkyl group, a cyano group, a bromine group, a chlorine group, a phenyl group, a 2-naphthyl group and a hydrogen atom; The side chain substituent R of the polymer 2 One selected from the group consisting of cyano, bromine, chlorine, methanesulfonyl, ethylsulfonyl, benzenesulfonyl, formyl, acetyl, benzoyl, phenyl, 2-naphthyl, 3-cyclopentanesulfonyl, 4-cyclopentanesulfonyl and hydrogen; Optionally, the main chain substituent R of the polymer 1 and the side chain substituent R 2 The type of R affects the mobility of polymer molecules, and further affects the mechanical strength and glass transition temperature of the polymer. Among them, the introduction of aromatic groups and polar groups will increase the glass transition temperature of the polymer, and the aromatic groups can increase the rigidity of the molecular chain due to their rigidity and the presence of π electron clouds, thereby increasing the glass transition temperature; the polar groups further strengthen the interaction between molecules by forming hydrogen bonds or other strong dipole interactions, resulting in an increase in the glass transition temperature. In addition, the present invention further prefers that the side chain substituent R 2 The introduction of polar groups, especially sulfonyl, acyl or cyano groups, on the acrylic polymer can improve the wettability of the electrolyte to the acrylic polymer through the dipole effect; Preferably, the main chain substituent R of the polymer 1 Selected from C 1 -C 3 One of alkyl, cyano, phenyl and 2-naphthyl.

[0009] Preferably, the side chain substituent R of the polymer 2 It is selected from one of cyano, methanesulfonyl, benzenesulfonyl, phenyl, 2-naphthyl, 3-cyclobutylsulfonyl and 4-cyclopentylsulfonyl.

[0010] Furthermore, the side chain of the polymer has a methylene group (CH 2 ) is 0~10.

[0011] Optionally, the role of the side chain in the polymer is to link the ester functional group of the polyacrylate and the side chain substituent R 2 , where the methylene group (CH 2 ) and the number x of side chain substituents R 2 It can be further limited to: when the side chain substituent R2 When the side chain substituent R is selected from phenyl, 2-naphthyl, 3-cyclobutylsulfone or 4-cyclopentylsulfone, x is 0 to 10; 2 When x is selected from cyano, bromine, chlorine, methanesulfonyl, ethylsulfonyl, benzenesulfonyl, formyl, acetyl, benzoyl or hydrogen atom, x is 1 to 10.

[0012] Optionally, the side chain of the polymer has a methylene group (CH 2 ) affects the mobility of the polymer side chain. The longer the side chain, the better the migration ability of the side chain and the lower the glass transition temperature.

[0013] Preferably, the side chain of the polymer has a methylene group (CH 2 ) is 0~3.

[0014] Furthermore, the number n of repeating units in the polymer is 1000-5000.

[0015] Optionally, a larger value of the number n of repeating units in the polymer represents a higher molecular weight of the polymer. At this time, due to the enhanced interaction between long-chain molecules, the glass transition temperature of the material increases, the strength and toughness increase, and the mechanical properties of the polymer are improved.

[0016] Another object of the present invention is to provide a method for preparing the modified acrylate polymer, comprising the following steps: (1) adding a substrate A represented by formula (2), a substrate B represented by formula (3) and a base into a solvent X for reaction, and then separating and purifying the obtained reaction product with an extractant to obtain a modified acrylate monomer represented by formula (4);

[0017] (2) Adding the modified acrylic ester monomer and the auxiliary agent into solvent Y for reaction, and then separating and drying the obtained reaction product to obtain the modified acrylic ester polymer.

[0018] Among them, R in formula (2) 3 Selected from C 1 -C 10 is one of an alkyl group, a cyano group, a bromine group, a chlorine group, a phenyl group, a 2-naphthyl group and a hydrogen atom; R in formula (3) 4 is selected from the group consisting of cyano, bromine, chlorine, methanesulfonyl, ethylsulfonyl, benzenesulfonyl, formyl, acetyl, benzoyl, phenyl, 2-naphthyl, 3-cyclobutylsulfone, 4-cyclopentylsulfone and hydrogen; the methylene group (CH 2 ) is 0~10.

[0019] Preferably, R in formula (2) 3 Selected from C1 -C 2 alkyl, cyano, phenyl or 2-naphthyl; preferably, R in formula (3) 4 is selected from one of cyano, methanesulfonyl, ethylsulfonyl, benzenesulfonyl, phenyl, 2-naphthyl, 3-cyclobutylsulfone or 4-cyclopentylsulfone; preferably, the side chain methylene (CH 2 ) is 0~3.

[0020] Optionally, in the method for preparing the polymer, the substituent R in the structure of substrate A and substrate B is 3 , Substituent R 4 and methylene (CH 2 ) remains unchanged during the preparation process, which is consistent with the modified acrylate monomer shown in formula (4) and the modified acrylate polymer finally prepared.

[0021] Optionally, the base in step (1) is selected from one or a combination of two or more of sodium carbonate, potassium carbonate, sodium hydroxide, potassium hydroxide, triethylamine and 4-dimethylaminopyridine; preferably, the base in step (1) is triethylamine.

[0022] Optionally, the solvent X in step (1) is selected from one or a combination of two or more of dichloromethane, chloroform, toluene and N,N-dimethylformamide; preferably, the solvent X in step (1) is dichloromethane.

[0023] Optionally, the extractant in step (1) is selected from one or a combination of two or more of dichloromethane, chloroform, ethyl acetate and diethyl ether; preferably, the extractant in step (1) is dichloromethane.

[0024] Optionally, the auxiliary agent in step (2) is selected from one or a combination of two or more of azobisisobutyronitrile, azobisisoheptanenitrile and dibenzoyl peroxide; preferably, the auxiliary agent in step (2) is azobisisobutyronitrile.

[0025] Optionally, the solvent Y in step (2) is selected from one or a combination of two or more of N,N-dimethylformamide, methanol and acetone; preferably, the solvent Y in step (2) is N,N-dimethylformamide.

[0026] Optionally, the molar ratio of substrate A to substrate B in step (1) is 10:1 to 1:10; preferably, the molar ratio of substrate A to substrate B in step (1) is 2:1 to 1:2.

[0027] Optionally, the molar ratio of substrate A to base in step (1) is 1:1-1:10; preferably, the molar ratio of substrate A to base in step (1) is 1:1-1:2.

[0028] Optionally, the concentration of substrate A in solvent X in step (1) is 0.1 mol / L to 5.0 mol / L; preferably, the concentration of substrate A in solvent X in step (1) is 0.5 mol / L to 1.0 mol / L.

[0029] Optionally, the amount of the additive added in step (2) is 1 wt% to 10 wt% of the modified acrylate monomer; preferably, the amount of the additive added in step (2) is 2 wt% to 5 wt% of the modified acrylate monomer.

[0030] Optionally, in step (2), the concentration of the modified acrylate monomer in solvent Y is 0.1 mol / L to 5.0 mol / L; preferably, in step (2), the concentration of the modified acrylate monomer in solvent Y is 0.5 mol / L to 1.0 mol / L.

[0031] Optionally, the reaction temperature in step (1) is 0°C to 100°C; preferably, the reaction temperature in step (1) is 20°C to 50°C.

[0032] Optionally, the reaction time in step (1) is 8 h to 24 h; preferably, the reaction time in step (1) is 8 h to 12 h.

[0033] Optionally, the reaction temperature in step (2) is 0°C to 100°C; preferably, the reaction temperature in step (2) is 60°C to 80°C.

[0034] Optionally, the reaction time in step (2) is 8 h to 24 h; preferably, the reaction time in step (2) is 8 h to 12 h.

[0035] Optionally, the drying temperature in step (2) is 60°C to 150°C; preferably, the drying temperature in step (2) is 80°C to 100°C.

[0036] Optionally, the drying time in step (2) is 12 h to 96 h; preferably, the drying time in step (2) is 24 h to 72 h.

[0037] Another object of the present invention is to provide a modified acrylate polymer as described above, or a modified acrylate polymer prepared by the above preparation method, for use in a lithium-ion battery separator coating material.

[0038] Optionally, the preparation method of the lithium-ion battery separator includes the following steps: using the modified acrylate polymer as described above to prepare a lithium-ion battery separator coating material, and coating it on both sides of a commercial polyolefin separator by electrospinning, and hot pressing to form a double-sided coating-modified lithium-ion battery separator.

[0039] Optionally, the specific preparation steps are as follows: (1) The modified acrylate polymer is added into N,N-dimethylformamide and stirred to dissolve to obtain an electrospinning solution.

[0040] (2) The electrospinning solution is added into a syringe, a commercial diaphragm is placed on a receiving roller for electrospinning, and the composite membrane is collected. The collected composite membrane is then placed in a vacuum drying oven for treatment at room temperature and reduced pressure until no solvent remains.

[0041] (3) The dried diaphragm with the modified coating on one side is again placed on the receiving roller, with the unspun side exposed, and electrospinning is performed again at an appropriate voltage, receiving distance and extrusion speed. The composite membrane is collected and then placed in a vacuum drying oven at room temperature and reduced pressure until no solvent remains.

[0042] (4) The dried composite film is subjected to five hot rolling processes and one hot pressing process to obtain a coating-modified lithium-ion battery separator.

[0043] Compared with the prior art, the modified acrylic polymer provided by the present invention and its preparation and application have the following beneficial effects: (1) The modified acrylate polymer provided by the present invention has a simple preparation method, is easy to synthesize, has a high reaction product yield, has a low preparation cost, has excellent environmental performance, and has both excellent high temperature resistance and good electrolyte wetting performance.

[0044] (2) The lithium-ion battery separator coating prepared using the modified acrylate polymer provided by the present invention has good electrolyte infiltration performance, can reduce the internal resistance of the battery, and improve the battery's rate performance and discharge capacity.

[0045] (3) The lithium-ion battery separator coating prepared using the modified acrylate polymer provided by the present invention has good high temperature resistance and can improve the safety and reliability of the battery in a high temperature environment or when overheated. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is the morphology of the composite diaphragm modified with the A-1-9 coating material prepared in Example 10 of the present invention. DETAILED DESCRIPTION

[0047] In order to further illustrate the present invention, the following examples are listed based on experimental results, but they do not limit the scope of the invention defined by the claims of the present invention.

[0048] Example 1 This example illustrates the preparation of poly (2-cyano)ethyl methacrylate.

[0049] The preparation method of the modified acrylate polymer of this embodiment comprises the following steps: (1) 40 mmol of methacryloyl chloride, 20 mmol of cyanoethanol and 80 mmol of triethylamine (Et 3 N) were dissolved in 80 mL of dichloromethane (CH 2 Cl 2 ) and then stirred at 20 °C for 12 h.

[0050] (2) After the reaction is completed, water is added to quench the reaction, and then the product is extracted with dichloromethane. The solvent is then evaporated to obtain the polymer monomer.

[0051] (3) The polymer monomer prepared in step (2) and azobisisobutyronitrile (AIBN) were dissolved in 80 mL of N,N-dimethylformamide (DMF), and then stirred at 60 °C for 12 h, wherein the amount of azobisisobutyronitrile added was 2 wt% of the modified acrylate monomer.

[0052] (4) The solid product was separated and dried at 80 °C for 72 h to obtain poly(2-cyano)ethyl methacrylate, denoted as A-1-1, with a reaction yield of 82%.

[0053] The reaction route of the modified acrylate polymer of this embodiment is as follows:

[0054] Example 2 This example illustrates the effect of different substrate concentrations on the preparation of poly (2-cyano)ethyl methacrylate.

[0055] The difference between this embodiment and embodiment 1 is that the amount of dichloromethane added in step (1) is set to 8 mL, 40 mL, and 400 mL, respectively, and the rest is the same as embodiment 1.

[0056] The yields of the polymers prepared under different substrate concentration conditions were analyzed, and the results are shown in Table 1.

[0057] Table 1 Effect of different substrate concentrations on the preparation of poly (2-cyano)ethyl methacrylate

[0058] Example 3 This example illustrates the effect of different molar ratios of substrate A to substrate B on the preparation of poly (2-cyano)ethyl methacrylate.

[0059] The difference between this embodiment and embodiment 1 is that the amount of cyanoethanol added in step (1) is set to 4 mmol, 80 mmol, and 400 mmol, respectively, and the rest is the same as embodiment 1.

[0060] The yields of the polymers prepared under different molar ratios of substrate A to substrate B were analyzed, and the results are shown in Table 2.

[0061] Table 2 Effect of different molar ratios of substrate A to substrate B on the preparation of poly (2-cyano)ethyl methacrylate

[0062] Example 4 This example illustrates the effect of different molar ratios of substrate A to base on the preparation of poly (2-cyano)ethyl methacrylate.

[0063] The difference between this embodiment and embodiment 1 is that the amount of triethylamine added in step (1) is set to 40 mmol and 400 mmol respectively, and the rest is the same as embodiment 1.

[0064] The yields of the polymers prepared under different molar ratios of substrate A to base were analyzed, and the results are shown in Table 3.

[0065] Table 3 Effect of the amount of triethylamine on the preparation of poly(2-cyano)ethyl methacrylate

[0066] Example 5 This example illustrates the effect of different esterification reaction temperatures on the preparation of poly (2-cyano)ethyl methacrylate.

[0067] The only difference between this embodiment and embodiment 1 is that the reaction temperature in step (1) is set to 10°C, 30°C, and 100°C, respectively, and the rest is the same as embodiment 1.

[0068] The yields of the polymers prepared under different esterification reaction temperature conditions were analyzed, and the results are shown in Table 4.

[0069] Table 4 Effect of different esterification reaction temperatures on the preparation of poly (2-cyano)ethyl methacrylate

[0070] Example 6 This example illustrates the effect of different additive amounts on the preparation of poly(2-cyano)ethyl methacrylate.

[0071] The difference between this embodiment and embodiment 1 is that the addition amount of azobisisobutyronitrile in step (3) is set to 1 wt%, 3 wt% and 10 wt% of the modified acrylate monomer respectively, and the rest is the same as embodiment 1.

[0072] The yields of the polymers prepared under different additive addition conditions were analyzed, and the results are shown in Table 5.

[0073] Table 5 Effect of the mass ratio of azobisisobutyronitrile to monomer on the preparation of poly(2-cyano)ethyl methacrylate

[0074] Example 7 This example illustrates the effect of different polymerization temperatures on the preparation of poly (2-cyano)ethyl methacrylate.

[0075] The only difference between this embodiment and embodiment 1 is that the polymerization reaction temperature in step (3) is set to 50°C, 80°C, and 100°C, respectively. The rest is the same as embodiment 1.

[0076] The yields of the polymers prepared under different polymerization reaction temperature conditions were analyzed, and the results are shown in Table 6.

[0077] Table 6 Effect of polymerization temperature on the preparation of poly(2-cyano)ethyl methacrylate

[0078] Example 8 This example illustrates the effect of different substrates B on the preparation of poly (2-cyano)ethyl methacrylate.

[0079] Except for using a different type of substrate B to replace the cyanoethanol used in step (1) of Example 1, the rest is the same as Example 1.

[0080] Modified polyacrylates were prepared according to the method of Example 1. The yields of polymers prepared from different substrates B were analyzed. The results are shown in Table 7.

[0081] Table 7 Labeling and yield of different substrates B and the corresponding polymers

[0082] Example 9 This example illustrates the effect of different substrates A on the preparation of poly (2-cyano)ethyl methacrylate.

[0083] The process was the same as in Example 1 except that a different type of substrate A was used instead of methacryloyl chloride used in step (1) of Example 1, and 20 mmol of 3-hydroxycyclopentane sulfone was used instead of 20 mmol of cyanoethanol used in step a).

[0084] Modified polyacrylates were prepared according to the method of Example 1. The yields of polymers prepared from different substrates A were analyzed. The results are shown in Table 8.

[0085] Table 8 Labeling and yield of different substrates A and the corresponding polymers

[0086] Example 10 This example illustrates the use of the modified polyacrylates prepared in Example 8 and Example 9 to modify the coating of a lithium-ion battery separator. The specific steps are as follows: a) The modified polyacrylates prepared in Example 8 and Example 9 were respectively added into N,N-dimethylformamide and stirred for dissolution for 12 h to obtain electrospinning solutions.

[0087] b) The above electrospinning solution was added into a syringe, and a commercial diaphragm was covered on the receiving roller. Electrospinning was performed under the conditions of 18 kV voltage, 20 cm receiving distance and 20 mm stroke. The composite membrane was collected and then placed in a vacuum drying oven under reduced pressure at room temperature until no solvent remained.

[0088] c) The dried diaphragm with the modified coating on one side is again placed on the receiving roller, with the unspun side exposed, and electrospinning is performed again at an appropriate voltage, receiving distance and extrusion speed, and the composite membrane is collected. The collected composite membrane is then placed in a vacuum drying oven and treated under reduced pressure at room temperature until no solvent remains.

[0089] d) The dried composite film is subjected to five hot rolling processes and one hot pressing process to obtain a coating-modified lithium-ion battery separator.

[0090] Figure 1 This is the morphology of the composite diaphragm modified with A-1-9 as the coating material in this example.

[0091] Embodiment 11 This example illustrates the liquid absorption and liquid retention performance tests of the lithium ion battery separator containing the modified polyacrylate coating prepared in Example 10.

[0092] The test method for the liquid absorption rate of the coating-modified lithium-ion battery separator is as follows: The coated lithium-ion battery separator is immersed in an electrolyte (LiPF 6=1.0 mol / L, EC / DEC / DMC=1 / 1 / 1) for 1 h, take it out and weigh it as the mass after immersion, where: Liquid absorption rate (%) = (mass after immersion - mass before immersion) / mass before immersion * 100% The test method for the liquid retention rate of the coating-modified lithium-ion battery separator is as follows: The coating-modified lithium-ion battery separator that has been immersed in the electrolyte for 1 h is used to absorb the excess electrolyte on the surface with a non-woven fabric and weighed as the liquid retention mass, where: Liquid retention rate (%) = (liquid retention mass - mass before immersion) / mass before immersion * 100% The test results of liquid absorption and liquid retention performance are summarized as follows: Table 9 Test results of liquid absorption and liquid retention performance

[0093] Example 12 In this example, the temperature resistance of the lithium-ion battery separator containing the modified polyacrylate coating prepared in Example 10 was tested.

[0094] The temperature resistance of the coating-modified lithium-ion battery separator was tested by a heat shrinkage experiment, where: Shrinkage rate (%) = diaphragm length after heat treatment / diaphragm length before heat treatment * 100% The results of the heat shrinkage experiments are summarized as follows: Table 10 Temperature resistance test

[0095] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A modified acrylic ester polymer, characterized in that: The structure of the polymer is shown in formula (1): Wherein, the main chain substituent R1 of the polymer is selected from C1-C 10 One of an alkyl group, a cyano group, a bromine group, a chlorine group, a phenyl group, a 2-naphthyl group and a hydrogen atom; The side chain substituent R2 of the polymer is selected from one of cyano, bromine, chlorine, methanesulfonyl, ethylsulfonyl, benzenesulfonyl, formyl, acetyl, benzoyl, phenyl, 2-naphthyl, 3-cyclopentanesulfone, 4-cyclopentanesulfone and hydrogen atom; The number x of methylene groups (CH2) in the side chain of the polymer is 0 to 10; The number n of repeating units in the polymer is 1000-5000.

2. A method for preparing a modified acrylate polymer as claimed in claim 1, characterized in that: The following steps are involved: (1) adding a substrate A represented by formula (2), a substrate B represented by formula (3) and a base into a solvent X for reaction, and then separating and purifying the obtained reaction product with an extractant to obtain a modified acrylate monomer represented by formula (4); (2) Adding the modified acrylic ester monomer and the auxiliary agent into solvent Y for reaction, and then separating and drying the obtained reaction product to obtain the modified acrylic ester polymer.

3. The preparation method according to claim 2, characterized in that: R3 in formula (2) is selected from C1-C 10 One of an alkyl group, a cyano group, a bromine group, a chlorine group, a phenyl group, a 2-naphthyl group and a hydrogen atom; R4 in formula (3) is selected from the group consisting of cyano, bromine, chlorine, methanesulfonyl, ethylsulfonyl, benzenesulfonyl, formyl, acetyl, benzoyl, phenyl, 2-naphthyl, 3-cyclopentanesulfonyl, 4-cyclopentanesulfonyl and hydrogen; The number x of methylene groups (CH2) in the side chain of substrate B is 0~10.

4. The preparation method according to claim 2, characterized in that: In the step (1), the base is selected from one or a combination of two or more of sodium carbonate, potassium carbonate, sodium hydroxide, potassium hydroxide, triethylamine and 4-dimethylaminopyridine; Solvent X is selected from one or a combination of two or more of dichloromethane, chloroform, toluene and N,N-dimethylformamide; The extractant is selected from one or a combination of two or more of dichloromethane, chloroform, ethyl acetate and ether.

5. The preparation method according to claim 2, characterized in that: In the step (2), the auxiliary agent is selected from one or a combination of two or more of azobisisobutyronitrile, azobisisoheptanenitrile and dibenzoyl peroxide; The solvent Y is selected from one or a combination of two or more of N,N-dimethylformamide, methanol and acetone.

6. The preparation method according to claim 2, characterized in that: In the step (1), the molar ratio of substrate A to substrate B is 10:1-1:10; the molar ratio of substrate A to base is 1:1-1:10; and the concentration of substrate A in solvent X is 0.1 mol / L-5.0 mol / L.

7. The preparation method according to claim 2, characterized in that: In the step (2), the amount of the additive added is 1 wt% to 10 wt% of the modified acrylate monomer; the concentration of the modified acrylate monomer in the solvent Y is 0.1 mol / L to 5.0 mol / L.

8. The preparation method according to claim 2, characterized in that: In the step (1), the reaction temperature is 0°C to 100°C; and the reaction time is 8 h to 24 h.

9. The preparation method according to claim 2, characterized in that: In the step (2), the reaction temperature is 0°C to 100°C; the reaction time is 8 h to 24 h; the drying temperature is 60°C to 150°C; and the drying time is 12 h to 96 h.

10. Use of the modified acrylate polymer according to claim 1, or the modified acrylate polymer prepared by the preparation method according to any one of claims 2 to 9 in a lithium ion battery separator coating material.

Citation Information

Patent Citations

  • Paint for lithium ion battery composite membrane and composite membrane using coating

    CN102993891A

  • Polymer composite film, preparation method thereof and lithium ion battery comprising same

    CN108242522A

  • Preparation method of high-adhesion coating diaphragm and prepared coating diaphragm

    CN110690390A

  • Composite diaphragm, preparation method thereof and sodium ion battery

    CN115347325A

  • Method for preparing highly absorptive polyvinyl alcohol, which comprises step of introducing ionic polymer into molecular chain of polyvinyl alcohol

    KR1019990043695A